Prediabetes and the risk of lung cancer incidence and mortality: A meta‐analysis - Enjian Shen; Xi Chen (Journal of Diabetes Investigation, 2023)
Abstract Aims/Introduction There has been conflicting evidence regarding the role of prediabetes as a risk factor of lung cancer. A systemic review and meta‐analysis was conducted to determine the relationship between prediabetes and lung cancer incidence and mortality in general adult populations. Materials and Methods Observational studies relevant to the objective were found in Medline, Embase, Cochrane Library, and Web of Science. By incorporating potential heterogeneity into the model, a randomized‐effects model was selected. Results Ten cohort studies were included. People with prediabetes were associated with a mildly increased risk of lung cancer incidence compared with controls with normoglycemia (risk ratio [RR]: 1.09, 95% confidence interval [CI]: 1.01–1.18, P = 0.03; I2 = 79%), which was mainly observed in men rather than in women (RR: 1.07 vs 0.99, P for subgroup difference < 0.001). Prediabetes was related to a higher risk of lung cancer mortality (RR: 1.19, 95% CI: 1.02–1.39, P = 0.03; I2 = 52%), and the results were consistent in both men and women (P for subgroup difference = 0.67). The association between prediabetes and lung cancer incidence or mortality did not appear to be significantly affected by different definitions of prediabetes (P for subgroup difference = 0.27 and 0.37). Conclusions Prediabetes might be associated with a mildly increased risk of lung cancer incidence in men, but not in women. In addition, prediabetes may be related to a higher risk of lung cancer mortality in the adult population.